MgO-Coated Layered Cathode Oxide With Enhanced Stability for Sodium-Ion Batteries - Xue, Ling; Bao, Shuo; Yan, Ling; Zhang, Yi; Lu, Jinlin; Yin, Yansheng (Frontiers in Energy Research, 2022)
Na0.67Ni0.33Mn0.67O2 is a prospective layered cathode material for sodium-ion batteries owing to its low cost, ease of synthesis, and high specific capacity. However, due to direct contact with electrolytes during the cycling process, the cyclic stability is not satisfied. To address this issue, magnesium oxide (MgO) surface modification was performed in this study to improve the material’s cycling properties. MgO layers of various thicknesses were successfully coated onto the cathode, and their electrochemical performances were thoroughly investigated. Among the as-prepared samples, the 2 wt% MgO-coated sample demonstrated the best rate capability and cycling stability. It had an initial reversible discharge capacity of 105 mAh g−1 in the voltage range from 2.0 to 4.5 V at 0.2 C with a high cycle retention of 81.5%. Electrochemical impedance spectroscopy (EIS) results showed that the 2 wt% MgO-coated electrode had the highest conductivity due to the smaller charge transfer resistance (Rct) value. All the test results show that the MgO modification improves the electrochemical properties of Na0.67Ni0.33Mn0.67O2 cathode material. This research could lead to the development of a promising strategy for improving the electrochemical performance of next-generation sodium-ion batteries.